Мектеп география пәниниң методикалық машқалалары - Баллиева, Р.; Гайпова, Р.Т.; Есбергенова, С.А. (FAN va JAMIYAT, 2020)
The article is devoted to the discussion of some problems in teaching the subject «Geography» at general educational schools. The author of the article points to some shortcomings in textbooks in Geography.